IMPLIKASI KEWENANGAN PEMERINTAH DAERAH DALAM PENYELESAIAN SENGKETA HASIL PILKADES DESA TANJUNG KECAMATAN KOTO KAMPAR HULU - Rose, Sarah Nila; ,, Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Village Head Elections (Pilkades) are part of the democratic system implemented at the village level. In practice, Pilkades often lead to disputes, as occurred in Tanjung Village, Koto Kampar Hulu Subdistrict, Kampar District. This study aims to analyze the implementation of local government authority in resolving disputes over Pilkades results and the factors hindering this process. The research method used is a qualitative approach with data collection techniques in the form of interviews and documentation. The results of the study indicate that the authority exercised by the Kampar Regency Government in resolving Pilkades disputes in Tanjung Village has not been effective. The Kampar Regency Government has taken actions that are not in accordance with Kampar Regent Regulation Number 54 of 2019 concerning the Simultaneous Pilkades. These actions clearly violate Article 57(5) of Kampar Regent Regulation No. 54 of 2019. The implementation of the authority of the Kampar Regency Government regarding the resolution of Pilkades disputes in Tanjung Village has not been effective because it does not align with Edward III's implementation theory, as examined from the aspects of communication, resources, disposition, and bureaucratic structure. Keywords: Authority, Local Government, Disputes, Village Head Elections